Device closure of atrial septal defect with severe pulmonary hypertension in adults: Patient selection with early and intermediate term results. Issue 2 (22nd October 2018) - Dalvi, Bharat; Jain, Shreepal; Pinto, Robin
Abstract: Objective: To describe a subset of atrial septal defect (ASD) with severe pulmonary hypertension (PHT) that is suitable for closure. Background: As per American Heart Association/American College of Cardiology guidelines, ASD with elevated pulmonary artery pressure (PAP) and pulmonary vascular resistance (PVR) >2/3rd systemic is considered as a contraindication for closure. Methods: Patients with anatomically large ASD measuring >25 mm and a high probability of reversible pulmonary vascular disease were subjected to fenestrated device closure, despite severe PHT and elevated PVR. They were discharged on pulmonary vasodilators and were followed for 39.5 ± 8.5 months. Four patients had repeat cardiac catheterization. Results: Six patients underwent successful device closure of large ASD with severe PHT. Their basal Qp:Qs was 2.8 ± 0.3:1 while the systolic PAP and the PVR index (PVRI) were 102.6 ± 11.5 mm Hg and 9.6 ± 1.6 Wu m 2, respectively. Post 100% oxygen inhalation, the Qp:Qs increased to 3.5 ± 0.3:1, systolic PAP remained 103.5 ± 7.6 mm Hg while the PVRI dropped to 5.4 ± 1.1 Wu m 2 . The postballoon occlusion systolic PAP decreased to 86.6 ± 8.8 mm Hg. At the last follow‐up, their pulmonary artery systolic pressure by tricuspid regurgitation (TR) jet decreased from 105.6 ± 12.6 mm Hg to 45 ± 7.0 mm Hg. During follow‐up cardiac catheterization ( n = 4), the systolic PAP and PVRI were 55.7 ± 9.2 mm Hg and 3.2 ± 0.4, respectively. Conclusions: Patients with anatomically big defect and a large left to right shunt at baseline with a high probability of reversible PVR benefit with ASD closure and pulmonary vasodilators, despite significantly elevated PAP and PVRI.